Applying Higher Order Thinking Skill (HOTS) to Strengthen Students’ Religious Moderation at Madrasah Aliyah - Hasan Basri; Andewi Suhartini; Asep Nursobah; Uus Ruswandi (Jurnal Pendidikan Islam, 2022)
The study aims to analyze students' analytical abilities about religious moderation for religious worship through learning PAI (Pendidikan Agama Islam/Islamic Religious Education) at the State Madrasah Aliyah. This study uses a qualitative-quantitative approach with a survey method. The number of respondents to this study was 468 students of madrasah aliyah in West Java, Central Java and South Sulawesi. Data were collected using written tests and interviews. Data were analyzed using content analysis and descriptive statistics. The findings of this study indicate that studentrs’ religious moderation is strenthened in the teaching of Islamic aspects of Aqidah in madrasah aliyah through the development of higher-level thinking learning (HOTS) by connecting the values of moderation in aqidah in everyday life. These findings reinforce the urgency of learning in strengthening religious moderation through higher order thinking skills.